CYP2C19 variability and clinical outcomes of clopidogrel, proton pump inhibitors, and voriconazole in Southeast Asia: a systematic review and meta-analysis - Hardi, Harri; Barinda, Agian Jeffilano; Mahata, Liganda Endo; Fitrianti, Zahra (Frontiers in Pharmacology, 2025)
IntroductionPolymorphism in CYP2C19 is more prevalent in East Asia than in other regions of the world. However, no systematic review has analysed CYP2C19 variation in the Southeast Asian population. The understanding of variation may serve as a foundation for pharmacogenetic research and testing in this domain. Therefore, this meta-analysis aims to clarify the variability of CYP2C19 in Southeast Asia and its clinical implications for several medications, including clopidogrel, proton pump inhibitors (PPIs), and voriconazole.MethodsThis systematic review employed the keywords “CYP2C19” and “Southeast Asia country,” obtained from PubMed, Scopus, Web of Science, and Google Scholar. Single proportion meta-analyses of allele distribution were performed utilizing inverse variance analysis. Meta-analyses of clinical outcomes were performed using the Mantel-Haenszel method.Results and discussionBased on 72 found studies, this meta-analysis revealed that CYP2C19 allele distribution in Southeast Asians is predominantly similar to that in East Asians, except for Indian Singaporeans and Malaysians, who match South and Middle Asians, and Papuans, who are similar to the Oceania population. CYP2C19 variation in Southeast Asian populations correlates with different treatment responses to clopidogrel and PPIs. The incidence of major adverse cardiovascular events (MACE), hypoaggregation, and clopidogrel resistance increased among clopidogrel users with CYP2C19 intermediate and poor metabolizer phenotypes. The effectiveness of PPIs treatment for Helicobacter pylori also tends to decrease in normal and intermediate metabolizers compared to poor metabolizers. Additional high-quality studies, including RCTs of pharmacogenetic testing, are essential to encourage CYP2C19 testing in Southeast Asia.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=593116, CRD42024593116